2021
DOI: 10.1111/1365-2664.13932
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian species vary in their learned avoidance response to the deadly fungal pathogen Batrachochytrium dendrobatidis

Abstract: 1. Lethal and sublethal effects of pathogens should theoretically select for host avoidance of these pathogenic organisms. Some amphibians can learn to avoid the pathogenic fungus Batrachochytrium dendrobatidis (Bd) after one infectionclearance event.2. Here, we investigated whether four taxonomically distinct amphibians, Cuban tree frogs Osteopilus septentrionalis, southern toads Anaxyrus (Bufo) terrestris, greenhouse frogs Eleutherodactylus planirostris and pine woods tree frogs Hyla femoralis, exhibited any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In association with these transmission sources, exposure risk is further mediated by (i) the proximity to and relative density of infectious zoospores in the environmental pool [ 23 , 42 , 43 ], or (ii) the relative density and shedding rate of conspecifics that are in direct contact [ 44 ]. Clinically infected amphibians are anecdotally reported to give off a recognizable smell (likely associated with the metabolite putrescine; [ 28 ]), and there is currently some evidence to suggest that amphibians may be able to detect and actively avoid [ 1 , 45 ] infected conspecifics or other sources of infection thereby reducing exposure risk [ 46 ]. Regardless of potential avoidance behaviours, however, variable exposure risk is thought to be a confounder of resistance and tolerance measures.…”
Section: Why Do Infection Tolerance and Resistance Matter In Chytridi...mentioning
confidence: 99%
“…In association with these transmission sources, exposure risk is further mediated by (i) the proximity to and relative density of infectious zoospores in the environmental pool [ 23 , 42 , 43 ], or (ii) the relative density and shedding rate of conspecifics that are in direct contact [ 44 ]. Clinically infected amphibians are anecdotally reported to give off a recognizable smell (likely associated with the metabolite putrescine; [ 28 ]), and there is currently some evidence to suggest that amphibians may be able to detect and actively avoid [ 1 , 45 ] infected conspecifics or other sources of infection thereby reducing exposure risk [ 46 ]. Regardless of potential avoidance behaviours, however, variable exposure risk is thought to be a confounder of resistance and tolerance measures.…”
Section: Why Do Infection Tolerance and Resistance Matter In Chytridi...mentioning
confidence: 99%
“… 116 , 117 , 118 , 119 Equally, an understanding of mechanism has been essential to interpret important host behavioral responses to infection such as increased skin shedding 120 and thermoregulatory changes 121 to manage pathogen loads and learned avoidance of the pathogen. 122 Importantly, an understanding of mechanism has been central to the development of effective treatments for infected frogs 117 , 123 , 124 and to the management of chytridiomycosis in conservation-significant amphibian populations worldwide. 125 …”
Section: Case Studies That Demonstrate a Mechanistic Approachmentioning
confidence: 99%
“…Nonetheless, behavioural changes following exposure to a pathogen were seldom studied in amphibians. The handful of studies that did so (Kiesecker et al 1999; McMahon et al 2014; McMahon et al 2021; Le Sage et al 2022) reported that healthy individuals avoided infected conspecifics or contaminated surfaces and did not show generalized social distancing. Infected amphibians can show anorexia and lethargy (Gray et al 2009; Landsberg et al 2013), but whether these result in passive self-isolation and whether amphibians display active self-isolation is not yet known.…”
Section: Introductionmentioning
confidence: 99%